Report and findings of Committee of Enquiry into Breaches of International Law Relating to Intervention in Spain - Rathbone, Eleanor F. (Eleanor Florence), 1872-1946 ; et al; Noel-Baker, Philip Noel-Baker, Baron
1936-10-03 018b-0068-014 292/946/18b/68(xiv)